Utility Firm Performance & Executive Compensation - Ted Peterson; Kaiyuan Yang; Chenxi Lin (SAGE Open)
Corporate governance remains a focal point for policymakers, investors, academics, and the public. While existing research has delved into the relationship between chief executive officer (CEO) compensation and firm stock performance, the findings have been inconclusive. Notably, the investor-owned public utilities sector faces distinct governance challenges due to private and public pressures. In this study, we examine CEO pay within publicly traded large-cap U.S. utilities from 2016 to 2020, aiming to gauge performance. Our research design incorporates statistical procedures involving correlations and t-tests to analyze these relationships comprehensively. Over the specified period, the utility industry generally underperformed the S&P 500 benchmark. Our findings affirm a positive correlation between CEO compensation and stock performance providing both practical and scholarly implications. Particularly, an increase in CEO total compensation corresponds to improved stock performance. Additionally, we identify significant associations between CEO pay increments and the firm's performance relative to the utility index (VPU). We advocate for further investigation to validate these relationships across diverse time frames and even industries, emphasizing their significance.